2014
DOI: 10.1177/0733464814563606
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Home Perspectives on the Admission of Morbidly Obese Patients From Hospitals to Nursing Homes

Abstract: Purpose of the Study Care challenges have been described for hospitalized morbidly obese (MO) patients. These challenges likely persist post-discharge. As a result, nursing homes (NH) may be reluctant to admit these patients, potentially leaving them “stranded in hospitals” with subsequent health deterioration and increased costs. This study sought to identify issues NHs consider in admissions decisions for MO patients transitioning out of hospitals. Design and Methods: IRB-approved surveys were mailed to nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 31 publications
(39 reference statements)
1
27
0
Order By: Relevance
“…In a recent survey of nursing homes administrators, 31% of respondents reported that staffing was not adequate to care for morbidly obese residents (defined in this study as residents weighing 325 pounds or more), and a survey of hospital discharge planners found that 60% of respondents thought that nursing homes had staffing concerns regarding admission of someone with a BMI of 35 or more. 31,32 While this difference between available workforce and assistance needed may have be compensated for by new methods or technology, it is most likely that staff are using a greater proportion of time and energy caring for the intensive needs of residents with obesity. Resident obesity is leading to a serious workforce issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent survey of nursing homes administrators, 31% of respondents reported that staffing was not adequate to care for morbidly obese residents (defined in this study as residents weighing 325 pounds or more), and a survey of hospital discharge planners found that 60% of respondents thought that nursing homes had staffing concerns regarding admission of someone with a BMI of 35 or more. 31,32 While this difference between available workforce and assistance needed may have be compensated for by new methods or technology, it is most likely that staff are using a greater proportion of time and energy caring for the intensive needs of residents with obesity. Resident obesity is leading to a serious workforce issue.…”
Section: Discussionmentioning
confidence: 99%
“…3537 In the previously mentioned survey of Pennsylvania nursing homes, 68% of respondents reported concerns about the specialized equipment needed for morbidly obese residents in their nursing home. 31 Among hospital discharge administrators, 72% of respondents reported perceived nursing home concerns regarding equipment necessary for care for residents with a BMI of 35 or more. 32 Such equipment is expensive to purchase or lease, and it may be difficult to justify for nursing homes with lower numbers of residents with obesity, leading nursing homes with less equipment, staffing, or volume to refuse admission to these prospective residents.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, both nursing home and hospital administrators have cited patient size as a factor increasing the difficulty of nursing home placement. 23,24 Without compensation for staffing and other resources used to treat residents with obesity, higher quality facilities may be less likely to admit these patients. Ultimately, this places a greater burden on lower-tier, resource-strained nursing homes, contributing to the spiral of poor quality and high turnover across these facilities.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study surveyed 360 nursing home directors of nursing to identify issues they consider when making admission decisions for patients who are severely obese and transitioning from an acute care hospital (Felix, Bradway, Ali, & Li, 2016). Although two-thirds of respondents reported patient size as an admission barrier, only 6% reported that patients who were severely obese were always refused admission.…”
Section: Care Transitions Persons Who Are Obese and Healthcare Provmentioning
confidence: 99%